Teksty reklamy telewizyjnej - Michalewski, Kazimierz (Acta Universitatis Lodziensis. Folia Linguistica, 1995)
Short advertisement films occupy a large part (especially around the peak viewing hours) of everyday programmes of the Polish stale television. Even though it is possible to imagine an advertisement film employing only extralinguistic means of communication, the advertisements in general, have so far been using written and spoken texts. The basic function of such a text and of the whole film is to encourage the viewers to buy the advertised product. However, independently of the sender’s intention, both the film and its text may have other functions The same text repeated many times can be stored in memory, and then called to mind, at least in fragments, just like certain belles-lettres expressions. As such, it can become an inviting and intrusive language pattern. The article concentrates on the most important, in the author’s view, features of television texts, their contents, composition, and syntax. It also justifies the need for a more detailed analysis of such texts.